2015
DOI: 10.1118/1.4927062
|View full text |Cite
|
Sign up to set email alerts
|

Age at exposure and attained age variations of cancer risk in the Japanese A‐bomb and radiotherapy cohorts

Abstract: The standard functions for risk effect modification by age, based on the A-bomb survivor data, predict second cancer risk in radiotherapy patients for ages at exposure prior to 40 yr and attained ages before 55 yr reasonably well. However, for larger ages, the refined and extended models can be applied to predict the risk as a function of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…For the LSS alone, the preferred ERR model was dependent on attained age, but essentially independent on age at exposure after correcting for attained age (Preston et al 2007 ; Brenner et al 2018 ). Comparing different RT studies, Schneider and Walsh ( 2015 ) found a decreasing risk with increasing age at exposure; however, no data were available for persons with age at exposure of 50 years or older. A more detailed discussion on these points can be found in Eidemüller et al ( 2021 ) and the corresponding supplement.…”
Section: Discussionmentioning
confidence: 99%
“…For the LSS alone, the preferred ERR model was dependent on attained age, but essentially independent on age at exposure after correcting for attained age (Preston et al 2007 ; Brenner et al 2018 ). Comparing different RT studies, Schneider and Walsh ( 2015 ) found a decreasing risk with increasing age at exposure; however, no data were available for persons with age at exposure of 50 years or older. A more detailed discussion on these points can be found in Eidemüller et al ( 2021 ) and the corresponding supplement.…”
Section: Discussionmentioning
confidence: 99%
“…For the definition of the risk profiles and baseline risk calculation (Table 1), we followed Brenner et al [24] for major coronary events and the risk prediction formula from Bach et al [25] for baseline risks of lung cancer. Regarding secondary contralateral BC, radiation-induced secondary BC is assumed to be mainly relevant for exposure at younger ages [26-28]. Therefore, an intermediate 10-year baseline risk was estimated for a woman aged 40 years using the Tyrer-Cuzick model [29].…”
Section: Methodsmentioning
confidence: 99%
“…However, how complexity of the initial lesion impacts down-stream events that inform cancer susceptibility in old vs. young individuals has not been defined. Breast cancer risk appears to decrease with increasing age of radiation exposure not only for A bomb survivors but also for radiotherapy cohorts [7]. The mechanistic underpinnings of these age-related differences in radiation-induced breast cancer susceptibility are not well understood.…”
Section: Introductionmentioning
confidence: 99%